Review on the Protective Mechanism of Pueraria Lobata and Hovenia Dulcis Extracts against Alcoholic Liver Injury - Yue, Xinyi; Luo, Jianguo; Chen, Xianliang; Xu, Bing (International Journal of Public Health and Medical Research, 2025)
Alcoholic liver injury is a disease that causes significant harm to the human body and is difficult to cure. Long - term heavy drinking and alcoholism can lead to alcoholic liver injury, triggering physical and mental related diseases, such as liver diseases, pancreatitis, dementia, and various types of cancer. Pueraria lobata and Hovenia dulcis have remarkable effects in combating alcoholic liver injury, and their action mechanisms are diverse. Their extracts can reduce ethanol - induced in vitro liver injury and play a key role in antioxidation, anti - inflammation, regulating cell apoptosis, and enhancing liver function, providing strong support for the prevention and treatment of alcoholic liver diseases. This study investigated the effect of the water extract of the Pueraria Lobata - Hovenia Dulcis herb pair on alcoholic liver injury in mice, aiming to provide new treatment options for the clinical treatment of alcoholic liver injury.